Relationship of the Quantity of Blood Lead Levels and the Knowledge, Work Practice, and Attitude of Workers in a Recycling Battery Factory in Nakhonsawan Province - Keadthongthawee, Santi; Havanond, Piyalamporn (Applied Environmental Research, 2013)
This research was a cross-sectional study. The purpose was to study relationship between knowledge, work practice and attitude of workers toward quantity of lead in their blood. The study took place during January-December 2008 in a recycling battery factory in Nakhonsawan Province by means of purposive sampling. Relevant data were gathered by structured questionnaire which was tested for reliability by means of Cronbach’s alpha coefficient. Analysis of the relationship was performed via Pearson’s product-moment correlation coefficient. The statistical significance was considered when p < 0.05. The results of the study of total 72 workers were as followings: average score of knowledge was 12.8 out of 15 with the SD of 1.6, max score of 15 and min score of 9; average behavior score of workers was 12.9 out of 15 with SD of 1.3, max score of 15 and min score of 9; average score on attitude was 22.7 out of 30 with SD of 0.94, max score 25 and min score of 21. Hence, majority of them were in good knowledge (86.1 %) and had good work practice (93.1 %). As well, all workers (100 %) had good attitude. Significant (p < 0.05) relationship between levels of lead in blood and behavior of workers was found. The workers with high quantity of lead in their blood stream took more precaution on their work practice. This might be the fact that they knew that lead in blood could naturally be released by mechanism of body. Furthermore, the condition could be improved if they do not obtain further lead. On the other aspect, the relationship between age and level of lead in blood is also significant (p < 0.001). The workers with older age had more quantity of lead in blood than young workers. However, there was no relationship among quantity of lead in blood toward attitude or knowledge of the workers. From the study, it is suggested that annual blood test and physical examination of all workers should be implemented. Furthermore, it should emphasize on the campaign of good work practice. Especially, smoking during working hour must be strictly prohibited, since the protection mask has to be taken off and open the chance of taking the lead in.